A new instrument for assessing the experience of dying and death in the intensive care units from the perspective of relatives - Andresen, Max; Andresen-Vasquez, Max (Journal of Thoracic Disease, 2016)
Post-traumatic stress disorder (PTSD) is defined as an anxiety disorder that generally follows exposure to extreme stress through either the threat of, or actual violence that can be physically harmful or life-threatening. It may be triggered, among other things, by natural disasters, assault or critical illness. An individual may react with intense fear, a sense of horror and helplessness. This changed state is characterised by three types of symptoms: constantly re-living the experience, evasive behaviour and exaggerated responses. These symptoms last for more than a month and may be accompanied by depression, characterised by feeling low and having no motivation and a lack of interest in things for a period lasting more than two months (1,2).